Community Participation Model of Health Promotion for the Elderly in Bangphlat District, Bangkok Metropolis - วงศ์วิเศษกุล, ผู้ช่วยศาสตราจารย์ ดร.ศรีสุดา; สุขเจริญ, พิไลพร; พยอมยงค์, นางสมจิตร์ (Journal of Food Health and Bioenvironmental Science, 2017)
This community based, mixed method research consisted of a quantitative study to explore health promotion lifestyle of the ageing. 330 elderly, obtained by proportional stratified sampling, were recruited as the sample group. The data was collected by the 52- item questionnaire and was analyzed by mean and standard deviation. To develop the Community Participation Model of Health Promotion for the Elderly in Bangphlat District, Bangkok Metropolis, a qualitative study was conducted with 15 key informants who, by purposive inclusion, were the elderly in the community. Content analysis was employed to analyze data from enhancing engagement workshop meetings. The results revealed that behaviors that developed as health promotion lifestyles of the elderly were spiritual growth, stress management and interpersonal relationships. These health responsibility and nutrition behaviors happened often, but physical activity behavior only happened sometimes. The Community Participation Model of Health Promotion for the Elderly in Bangphlat District, Bangkok Metropolis consisted of: 1) raising community potentials in health promotion care 2) health promotion services and health risks screening 3) knowledge management on health promotion in community and 4) building the capacity of the elderly to be actively ageing. This model can be applied in other communities beyond this context.